Capacities in Generalized Orlicz Spaces - Debangana Baruah; Petteri Harjulehto; Peter Hästö (Journal of Function Spaces)
In this paper basic properties of both Sobolev and relative capacities are studied in generalized Orlicz spaces. The capacities are compared with each other and the Hausdorff measure. As an application, the existence of quasicontinuous representative of generalized Orlicz functions is proved.